Cultural proficiency a manual for school leaders - Lindsey, Randall B. (Corwin, 2019)
Our students' futures depend upon it: If we're to guarantee equitable access and improved academic outcomes for our historically underserved students, then we must first confront the deeply rooted biases and practices that for far too long have limited them. That's where Cultural Proficiency: A Manual for School Leaders has already benefited tens of thousands of schools leaders--and the students, teachers, and communities they serve. Cultural Proficiency helps us all establish a mindset and worldview for effectively describing and responding to inequities. Its inside-outside approach to leadership is grounded in the assumption that honest introspection is a requirement to leading equity-driven change. And now, with updated content, new case studies, expanded vignettes, new activities and study guides, and an updated matrix, this fourth edition is more urgently needed than ever. Take this first step on the Cultural Proficiency journey and soon enough you, too, can create equitable educational opportunities and more inclusive environments in which differences are embraced. -- Provided by publisher.